Expozició : Fotó/müvészet. (Hatvan : Hatvany Lajos Múzeum, 1976)
Bálint, Endre ; Gyarmathy, Tihamér ; Jakovits, József ; Lajos, Kassák ; Bak, Imre ; Birkas, Akos ; Csiky, Tibor ; Erdély, Miklós ; Hajas, Tibor ; Károly, Halász ; Tot, Endre ; Vetö, János
Expozició Fotó/müvészet, Hatvany Lajos Múzeum, Hatvan, 1976 október 24 - 1977 január 31.
boek